DOI: 10.14264/uql.2017.171
|View full text |Cite
|
Sign up to set email alerts
|

Residue management strategies for the rainfed N-deprived maize-legume cropping systems of central Mozambique

Abstract: Identifying best-fit residue management strategies for Central Mozambique rain fed Ndeprived maize-legume cropping (LEINA) systems managed under conservation agriculture is critical to improve resource use efficiency and yields. Therefore, understanding under what circumstances positive and negative responses from carbon rich residue mulches are likely to occur and what drives farmers' decision on the adoption of technologies is critical to design relevant and feasible recommendations that fit farmers complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 125 publications
(150 reference statements)
0
2
0
Order By: Relevance
“…A study conducted in a rainfed arid region of central Mozambique found a differential effect in the response to organic mulch applications, depending on the soil moisture holding capacity of the soils. Crop residue applications increased the WUE and NUE in soils with a low water holding capacity, while these variables were reduced when residues with a high C/N ratio were applied on soils with a high water holding capacity, apparently fixing the available N for their microbial decomposition [242].…”
Section: Water Use X N Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted in a rainfed arid region of central Mozambique found a differential effect in the response to organic mulch applications, depending on the soil moisture holding capacity of the soils. Crop residue applications increased the WUE and NUE in soils with a low water holding capacity, while these variables were reduced when residues with a high C/N ratio were applied on soils with a high water holding capacity, apparently fixing the available N for their microbial decomposition [242].…”
Section: Water Use X N Interactionsmentioning
confidence: 99%
“…Crop responses to N x water interactions Broccoli (tunnels), Cabbage; Greenhouse cucumbers; African eggplant (Solanum aethiopicum L,); Onions; tomato [239,[245][246][247]249,250] Cultivar selection Selection of early maturing cultivars during drought periods [251] Fertigation Improved NUE [24,171,238] Irrigation system selection Effect on moisture uniformity, WUE x N x yields [231,249] Irrigation rates and timing Irrigation x N interaction [239] Organic Mulches Reduced evapotranspiration and erosion; moderates soil temperature and moisture; N cycling [43,242] Plastic mulches Reduced evapotranspiration and erosion; moderates soil temperature and moisture [43,69] Rotations Water and NUE [243,244] Tillage Moisture retention under no-till farming and NUE [235]…”
Section: Interaction Variable Notes Referencesmentioning
confidence: 99%